FRI0422 Analysis of Seropositivity, Salivary Gland Ultrasonography and Histology in a Dedicated Primary Sjögren's Syndrome Clinic. (9th June 2015) - Batten, R.L.; Rahiman, I.; Ng, W.-F.
Abstract : Background: We reviewed investigation findings in new-patient referrals to a Primary Sjögren's Syndrome (PSS) clinic in the North East of England. The aim is to assess the role of salivary gland ultrasound (SGUS) and biopsy to support a timely diagnosis, and to consider its role in assessing disease activity and damage with a view to guiding management in patients with an established diagnosis of PSS. Objectives: We aim to inform service design, including the value of point-of-care US. With current research focusing on the value of immunomodulators to treat active disease and to prevent systemic damage, an effective diagnostic pathway is required to guide management, with the ultimate goal to improve the standard of care for PSS sufferers. Methods: A list of new suspected PSS referrals between January 2009 and September 2014 was obtained from the hospital database. Notes, including clinic letters, blood tests, SGUS reports and salivary gland (SG) histology reports were reviewed. 292 referrals have been audited. Results: The age at referral ranged from 16-89 (mean 58.4 years, median 59.0). Male to female ratio: 1:4.5. 138 patients had a diagnosis of PSS according to AECG criteria. 103 patients had abnormal US (score ≥0.5). 23 had a normal US (score=0). US sensitivity was 75% when compared to histology. 83 patients were found to be positive for anti-Ro and/or anti-La, 69 of these were diagnosed with PSS. Young age at presentation was associated with positive serology, with peaks at presentation at 26-30 years and 41-45 years. Seropositivity was associated with higher Focus Scores (FS) on biopsy and higher SGUS scores (range 0-5.5, mean 2.2, median 2.0), compared to seronegative patient SGUS scores (range 0-5, mean 1.0, median 0.5). Data for duration of symptoms was obtained for 133 patients with a diagnosis of PSS. 54.9% of patients presented after 5 years of symptoms. Longer duration of symptoms is associated with a higher FS. Conclusions: The findings from our analysis conform to the epidemiology for gender bias and age at presentation. We found that those who are Ro/La positive presented earlier and had more advanced changes on salivary gland ultrasound and histology. This group of patients may be at risk of earlier systemic damage and may benefit from rapid diagnosis and advanced management such as immunomodulatory therapy. Current evidence suggests that US is both specific and sensitive for detecting changes in the salivary gland. 1 It is a non-invasive and low-cost resource which may be used as an adjunct to SG biopsy. It does however require an experienced sonographer to interpret the images. Patients are currently referred to an outside department for SGUS. Specialty Trainees with an interest in PSS should be encouraged to gain experience in this field with a view to developing US as a bedside test within the clinic environment. This would be both financially beneficial and aid earlier diagnosis. Duration of symptoms at presentation is associated with a higher FS in this cohort. Education and awareness of PSS within the community and primary care should be on-going to assist earlier diagnosis. References: Tayeki Y et al. Extended report: Salivary gland ultrasonography: can it be an alternative to sialography as an imaging modality for Sjögren's syndrome? Published Online First: 24 May 2010 Disclosure of Interest: None declared